Electronic Word of Mouth dan Pengaruhnya pada Minat Beli Produk Ramah Lingkungan di Rokan Hulu - Toni Ahmad Subekti; Fitra Mulya; Nurmala Sari; Willi Meilita; Alfa Syahputra; Junifar Akmal (MOTIVASI, 2026)
Purpose– This study investigates the influence of electronic word of mouth (eWOM) on green purchase intention. Design/methodology– The type of research used is a quantitative approach. Data collection was conducted using a questionnaire administered via Google Forms. Respondents must meet the following criteria: be at least 16 years old and have used environmentally friendly products for at least the past three months. Instrument testing was conducted with 50 respondents. This study was conducted in Rokan Hulu Regency, Riau Province. This study used Structural Equation Modeling (SEM) with data from 300 respondents. Findings - The results of the study showed that eWOM Quality, eWOM Usefulness, eWOM adoption, and attitude toward eWOM have a significant positive effect on green purchase intention. However, eWOM credibility was found to have no significant effect on green purchases